2011
DOI: 10.5539/ijps.v3n2p156
|View full text |Cite
|
Sign up to set email alerts
|

Is Age-related Decline in Vocal Emotion Identification an Artefact of Labelling Cognitions?

Abstract: Evidence has emerged that older adults find it more difficult to interpret prosodic emotions than younger adults. However, typical tasks involve labelling-related cognitions over and above emotion perception per se. Accordingly, we aimed to determine if age-related difficulty in prosodic emotion labelling extended to discrimination, which is more closely related to emotion perception per se. For this purpose, 45 younger adults (mean age 20 years, 2 males/43 females) and 45 older adults (mean age 71 years, 16 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Further studies on this topic should build on our initial findings and perhaps examine the contribution of the perception of more complex acoustic correlates to age-related impairment in emotional prosody perception, for example, speech rate (Breitenstein et al, 2001) or pitch contour (Darwin & Hukin, 2000). Whatever its exact form, this sensory level of impairment adds to the demonstrations of ours and others that age-related impairment in prosodic emotion comprehension is not explained away by cognitive aging (Mitchell, 2007; Orbelo, Grim, Talbott, & Ross, 2005; Orbelo, Testa, & Ross, 2003), it is observed for the comprehension of emotional prosody as in the focus of the current study and for nonemotional prosody as examined in our other research (Mitchell et al, 2011), and it does not disappear when using processing tasks of reduced cognitive demand (Mitchell & Kingston, 2011). In short, the evidence seems to be suggesting that age-related impairment in prosodic emotion comprehension reflects a fundamental deficit at a basic level of processing.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Further studies on this topic should build on our initial findings and perhaps examine the contribution of the perception of more complex acoustic correlates to age-related impairment in emotional prosody perception, for example, speech rate (Breitenstein et al, 2001) or pitch contour (Darwin & Hukin, 2000). Whatever its exact form, this sensory level of impairment adds to the demonstrations of ours and others that age-related impairment in prosodic emotion comprehension is not explained away by cognitive aging (Mitchell, 2007; Orbelo, Grim, Talbott, & Ross, 2005; Orbelo, Testa, & Ross, 2003), it is observed for the comprehension of emotional prosody as in the focus of the current study and for nonemotional prosody as examined in our other research (Mitchell et al, 2011), and it does not disappear when using processing tasks of reduced cognitive demand (Mitchell & Kingston, 2011). In short, the evidence seems to be suggesting that age-related impairment in prosodic emotion comprehension reflects a fundamental deficit at a basic level of processing.…”
Section: Discussionsupporting
confidence: 78%
“…To answer the key question motivating this study, we then went back to our previous data on prosodic emotion discrimination in these participants (Mitchell & Kingston, 2011), and using SPSS Statistics v20 (IBM; Portsmouth, UK), implemented standard multiple regression analyses to determine how well our new basic auditory perception data predicted prosodic emotion perception. In that prior study, we found the mean performance accuracy (mean ± SD ) of our younger adults across that emotion discrimination task was 71.7 (±10.87), and that of our older adults was 64.4 (±13.41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduced accuracy could be due to difficulties labeling and not to perceptual problems, per se (Orgeta, 2010; Ruffman, Ng, & Jenkin, 2009). However, the prosody-decoding abnormalities in older adults remain even in pairing tasks, which do not require labeling (Mitchell & Kingston, 2011). The distinction between labeling and pure perceptual problems has also been investigated among children: Emotion labeling in children with specific language impairment is less accurate than in controls, and this impairment may be attributed to semantic fields overlapping (Delaunay-El Allam, Guidetti, Chaix, & Reilly, 2011).…”
mentioning
confidence: 99%
“…Some evidence in the literature may support this sensory source, with a specific age-related deficit in prosodic processing that might not be accompanied by a similar deficit in spoken-word processing. Indeed, age-related decrease in the recognition of prosodic information has been widely reported, both in quiet and in noise ( Dmitrieva and Gelman, 2012 ; Lambrecht et al, 2012 ; Dupuis and Pichora-Fuller, 2014 , 2015 ; Ben-David et al, 2019 ), suggesting a specific deficit in decoding emotional prosody in aging ( Orbelo et al, 2005 ; Mitchell, 2007 ; Mitchell and Kingston, 2011 ). This prosodic deficit may relate to senescent changes in auditory brain areas and neural activity patterns ( Orbelo et al, 2005 ; Giroud et al, 2019 ; Myers et al, 2019 ; Grandjean, 2021 ).…”
Section: Introductionmentioning
confidence: 99%